PENGARUH HARI RAYA IDUL FITRI TERHADAP INFLASI DI INDONESIA DENGAN PENDEKATAN ARIMAX (VARIASI KALENDER) - Susila, Muktar Redy (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
The inflation rate is very important for the government to maintain the stability of the country's economy. If inflation cannot be controlled, the prices of goods and services will rise uncontrollably. Eid al-Fitr causes increase basic needs price. It is assumed that abnormal prices have an effect on inflation. The purpose of this study is to calculate the effect of Eid Al-Fitr to Indonesian monthly inflation. The ARIMAX (Calendar Variation) method is used to determine the effect of Eid Al-Fitr on Indonesian monthly inflation. The data used in this study is the monthly inflation by Badan Pusat Statistik. The characteristics of inflation in July 2008 to June 2019 are unique. The average of inflation is 0,39 and the variance of inflation is 0,26. The ARIMAX model shows that January, May, June, July, August, November, December, and Eid Al-Fitr has a significant effect on Indonesian monthly inflation. The effect of the Eid Al-Fitr was 0,47. The meaning of this number is that when Eid al-Fitr arrives, inflation will increase by 0,47.